Analysis of Capacitor Unbalance Protection activation due to AC filter tripping incident at ±660kV HVDC Lahore converter station - Muhammad Imran; Abdullah Naveed; Habib Ullah; Mohammad Ahsan Shehzad; Zhang Jianmeng (Journal of Engineering Research and Reviews)
This study examines an AC filter tripping incident that occurred at Lahore Converter station of ±660kV high voltage direct current (HVDC) Pak Matiari-Lahore transmission project which seriously affected the stable operation of the converter station. The fault current exceeded the trip threshold and lasted for more than 20 milliseconds, causing the activation of capacitor unbalance protection. The short circuit discharge phenomenon occurring between the layers of the capacitors is responsible for tripping the filter leading to the activation of capacitor unbalance protection. The incident emphasizes how important protection methods are to maintaining system stability in unusual circumstances. The fault mechanism is thoroughly examined, including its underlying causes and modes of transmission. In order to prevent the expensive equipment from damage, the study highlights the importance of precise protective settings. To reduce future dangers, suggestions are made for better operation and maintenance procedures and cutting-edge monitoring systems. By taking these measures, the AC filter's robustness and dependability will be improved, especially during difficult grid circumstances like periods of high demand. [J Eng Res Rev 2025; 2(2.000): 119-126]